Early Histone Deacetylase Inhibition Mitigates Ischemia/Reperfusion Brain Injury by Reducing Microglia Activation and Modulating Their Phenotype - Li, Shuyuan; Lu, Xiaoshuang; Shao, Qian; Chen, Zixin; Huang, Qiong; Jiao, Zinan; Huang, Xiaodi; Yue, Maosong; Peng, Jingwen; Zhou, Xin; Chao, Dachong; Zhao, Heng; et al. (Frontiers in Neurology, 2019)
Histone deacetylase inhibitors (HDACi) are a promising therapeutic intervention for stroke. The involvement of the anti-inflammatory effects of HDACi in their neuroprotection has been reported, but the underlying mechanisms are still uncertain. Given the post-stroke inflammation is a time-dependent process, starting with acute and intense inflammation, and followed by a prolonged and mild one, we proposed whether target the early inflammatory response could achieve the neuroprotection of HDACi? To test this hypothesis, a single dose of suberoylanilide hydroxamic acid (SAHA) (50 mg/kg), a pan HDACi, was intraperitoneally (i.p.) injected immediately or 12 h after ischemia onset in a transient middle cerebral artery occlusion (tMCAO) mouse model. Compared with delayed injection, immediate SAHA treatment provided more protection, evidenced by smaller infarction volume, and a better outcome. This protection was accompanied by suppression of pro-inflammatory cytokines and reduction of activated microglia in the early stage of post-stroke inflammation. Moreover, SAHA treatment suppressed M1 cytokine expression (IL-6, TNF-α, and iNOS) while promoted the transcription of M2 cytokines (Arg-1 and IL-10) in LPS-challenged mouse microglia, and enhanced CD206 (M2 marker) but decreased CD86 (M1 markers) levels in microglia isolated from the ipsilateral hemisphere of MCAO mice. Collectively, our data suggested that the protection of SAHA on ischemic brain injury was closely associated with its inhibition on the early inflammatory response, and this inhibition was related to its reducing microglia activation and priming the activated microglia toward a more protective phenotype.